Main reasons for medical consultations in family healthcare units in the city of Recife, Brazil: a cross-sectional study - Torres, Rinailda de Cascia Santos; Marques, Karine Sobral; Leal, Kamila de Nazaré Ribas; Rocha-Filho, Pedro Augusto Sampaio (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: Only a few studies have focused on the main reasons for consultations at primary healthcare units within the Family Health Program. The aim here was to describe the reasons that led patients to seek assistance at four primary healthcare units in the city of Recife, Brazil. DESIGN AND SETTING: Cross-sectional study at primary healthcare units in the city of Recife. METHODS: Among adult patients who were consecutively attended at four primary healthcare units in the city of Recife, their two main reasons for going there were recorded by medical students. The students did not interfere in the consultation dynamics. The data were gathered between September 2010 and March 2011 and between November 2012 and August 2013. The reasons for the consultations were grouped into broader categories in accordance with the International Classification of Primary Care (ICPC-2). RESULTS: 478 patients were included. Their mean age was 45.9 years (± 16 years) and 71% were female. Pain was the main reason for seeking medical attention (34%), followed by evaluation of tests, prescription renewal and medical certificates (17.6%). The most frequent types of pain were musculoskeletal pain (15.7%), headache (10.4%) and abdominal pain (8%). The main reasons for consultation according to ICPC-2 were in the general and nonspecific, musculoskeletal, nervous system-related and digestive tract categories. CONCLUSION: Pain was the most frequent reason for seeking medical attendance at these primary healthcare units.